Machine Learning vs. Human Investors: Analyzing Adaptive Herding Behavior in U.S. Stocks vs. Shariah-Compliant Stocks in Malaysia and Indonesia - Candra, Sevenpri; Kok Loang, Ooi (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2025)
This study examined the effectiveness of machine learning models in capturing adaptive herding behavior in the U.S., Malaysia, and Indonesia. Utilizing data from January 2010 to December 2023, the study incorporates market sentiment (Thomson Reuters MarketPsych indices), news sentiment (Bloomberg sentiment analysis), and investor happiness measures (Hedonometer). The methodology employs both static and adaptive herding analyses using the CSAD approach, enhanced by real-time sentiment analysis and various machine learning models, including single- and multi-layer neural networks. The results indicate significant differences in herding behavior across the three markets, with machine learning models demonstrating superior performance in capturing herding behavior and faster normalization after major macroeconomic events than traditional methods. These findings highlight the potential of machine learning models to challenge the static assumptions of the efficient market hypothesis and provide insights for designing better trading algorithms by considering the impact of market sentiment, news sentiment, and investor happiness.